2021
DOI: 10.1021/acsanm.1c02060
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Metastable Honeycomb Arrangement of C60 on Ni(111) with (7 × 7) Periodicity: Tailoring an Interface for Organic Spintronics

Abstract: Hybrid nanostructures in which organic molecules are interfaced with metal surfaces hold promise for the discovery of intriguing physical and chemical phenomena, as well as for the development of innovative devices. In this frame, it is crucial to understand the interplay between the structural details of the interface and the electronic properties of the system. Here, an experimental investigation of the C 60 /Ni(111) interface is performed by means of scanning tunneling microscopy/spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…For this reason, we did not try annealing at higher temperatures. Therefore, in this study, did not observe the recently reported (7 × 7) overlayer structure obtained by annealing at 670 K. 17 This structure is remarkably similar to the (7 × 7) phase we report above for C 60 /Co(0001). The identified adsorption sites are identical, with 2 of the C 60 in the unit cell in alternate 3-fold sites and the remaining C 60 in a 2-fold degenerate atop site.…”
Section: ■ Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…For this reason, we did not try annealing at higher temperatures. Therefore, in this study, did not observe the recently reported (7 × 7) overlayer structure obtained by annealing at 670 K. 17 This structure is remarkably similar to the (7 × 7) phase we report above for C 60 /Co(0001). The identified adsorption sites are identical, with 2 of the C 60 in the unit cell in alternate 3-fold sites and the remaining C 60 in a 2-fold degenerate atop site.…”
Section: ■ Methodssupporting
confidence: 88%
“…We describe in detail a (7 × 7) phase for unannealed C 60 /Co(0001), finding that the three C 60 molecules in the unit cell occupy three distinct adsorption sites: two hollow sites with 3-fold symmetry and one atop site with 6-fold symmetry. This is similar to the (7 × 7) C 60 / Ni(111) phase observed by Picone et al 17 In our measurements of C 60 /Ni(111), identification of the molecular orientations was not possible. Due to the similar lattice parameters of Co(0001) and Ni(111), we conclude that the perpendicular orientation is (7 × 7) on both substrates.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemisorption is the typical scenario for molecules stabilized on metallic substrates. Here, the hybridization between the molecular orbitals and the electronic states of the substrate generally modifies the intrinsic properties of the molecules, inducing the broadening of the molecular resonances, the narrowing of the band gap, and the development of interface states [ 15 16 ]. The ability to tailor the degree of electronic coupling between the molecules and the substrate is of utmost importance when it comes to embedding the interface in a specific application.…”
Section: Introductionmentioning
confidence: 99%